Inter-University International Collaboration for an Online Course - D.B. Turner; C. Igbrude; J. O'Connor (European Alliance for Innovation (EAI), 2016)
This paper is an account of a collaboration between two international partners in Europe and in USA. The authors outline the origin, design and implementation of an inter-university, online teaching experience. The processes are discussed along with participants' perspectives of the experience. No institutional changes or formal agreements were needed; the course was validated by each institution, designed to address the requirements of each. Responsibility for participant assessment remained with the home institution. Instructors used Web 2.0 technology to plan and implement the online course. Student perspectives include their previous international educational experience, if any, use of technology for personal and educational purposes, and reactions to their virtual collaboration with international students. The paper discusses issues of coordination, illustrates students' international experience and technology use, and makes recommendations for developing similar collaborations.